O Imaginário Social Mulher Brasileira> em Portugal: Uma Análise da Construção de Saberes, das Relações de Poder e dos Modos de Subjetivação - Mariana Selister Gomes (Universidade do Estado do Rio de Janeiro, 2013)
This article analyses <Brazilian women > in the social imaginary in Portugal through the Foucaultian analytical triad knowledge-power-subjectivation, combined with feminist and de-colonial perspectives. The article begins with a retrospective genealogy of media and touristic discourses, based on interviews and documents, in order to unveil the knowledge-power discursive order in the image of <Braz ilian women>. The second part analyzes subjectivations of Brazilian immigrant women in Portugal, drawing on interviews and participant observation, to unveil situations of prejudice and discrimination and shed light on how the women confront the discursive order by resisting and re-existing as subjects. According to the conclusions, Brazilian women are seen as a colonial body to the extent that they are defined, essentialized, and stigmatized through characteristics attributed to them ever since the historical colonial period an d related to hypersexuality. Three modes of subjectivation are identified by which these women resist stigma and re-exist: passive, affirmative, and combative resistance.